Desain Model Pembelajaran Pendidikan Agama Kristen bagi Anak - Yanwar Prawono (SIKIP: Jurnal Pendidikan Agama Kristen, 2020)
This study aims to identify the context in which PAK for children can be taught exactly where the child lives, grows, and mingles in their environment. The context referred to is the Christian Church in Luwuk Banggai (GKLB), specifically in the Imanuel Laonggo congregation. Knowing the context well will be very helpful in the hope of appropriate learning. The teaching of PAK for children refers to the teaching model of Jesus, and this has become the basis for the form of PAK Children's learning throughout the ages and places. If Jesus' teaching model was a text, it needed context. A text that touches the context will give birth to a living faith. Therefore, it is very important to design a children's PAK learning model in their respective contexts. What has been done through this research has actually stimulated the church institutionally to think and implement the contextual PAK learning mechanism for children through its ministry programs. This really helps children as the future church and the church in the future to grow and bear fruit for Christ in their context. Abstrak Penelitian ini bertujuan untuk mengenal konteks di mana PAK bagi anak dapat diajarkan dengan tepat di mana anak hidup, tumbuh dan bergaul dalam lingkungannya. Konteks yang dimaksud adalah Gereja Kristen di Luwuk Banggai (GKLB), secara khusus di jemaat Imanuel Laonggo. Mengenal konteks dengan baik akan sangat menolong dalam penarapan pembelajaran yang tepat. Pengajaran PAK bagi anak mengacu pada model pengajaran Yesus, dan hal Ini menjadi dasar bentuk pembelajaran PAK Anak di sepanjang zaman dan tempat. Bila model pengajaran Yesus adalah sebuah teks, maka ia membutuhkan konteks. Sebuah teks yang menyentuh konteks akan melahirkan sebuah iman yang hidup. Sebab itu sangat penting untuk mendesain suatu model pembelajaran PAK anak dalam konteksnya masing-masing. Apa yang dilakukan melalui penelitian ini sesungguhnya merangsang gereja secara institusional dapat memikirkan dan mengerjakan secara tepat mekanisme pembelajaran PAK anak yang kontekstual melalui program-program pelayanannya. Hal ini sangat menolong anak sebagai masa depan gereja dan gereja dimasa depan untuk bertumbuh dan berbuah bagi Kristus dalam konteksnya.